Customer Centric in Hospitality Industry: A Systematic Literature Review and Future Research Direction - Rini, Gilang Puspita; Ferdinand, Augusty Tae (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2021)
The purpose of this research is to review the literature published from 2010 to 2020 regarding customer-centric strategy in the context of the hospitality industry.Ã‚Â This is a literature review research with the Publish or Perish software used to obtain initial data from a total of 235 articles published from 2010-2020 according to the Scopus database. The articles were further analyzed according to the criteria, with only 87 articles. The results showed that a customer-centric strategy is a company strategy that pays attention to consumer wants and needs. The customer-centric approach is similar to the outside-in approach because they pay attention to customers and adjust their complaints to company policies and strategies. This research provides benefits for future studies on customer-centric strategy in the hospitality industry that uses big data analytics to create value for customers. Furthermore, it provides an overview of customer-centric strategy trends in terms of understanding, theoretical perspective, and setting needed for future studies.